2003
DOI: 10.1021/jp0361125
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Calculations of Bond Dissociation Enthalpies with Density Functional Methods

Abstract: C-halogen) have been computed by using five density functional methods (B3LYP, MPW1PW91, B3PW91, B3P86, and MPW1P86). The quality of these methods is comprehensively evaluated on the basis of the available experimental bond dissociation enthalpies, and it is found that the MPW1P86 has the best agreement, while B3LYP performs the largest deviations. Large deviations also are found at the sophisticated CCSD(T) level of theory. The restricted open-shell method underestimates the radical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 51 publications
9
73
1
2
Order By: Relevance
“…In general it appears when a first-row atom or group X (X = B, C, N) is successively alkylated. Gilbert [3] found increasing errors of the B3LYP functional (up to 20 kcal mol À1 ) for the dissociation reaction (1) when R = H is replaced by CH 3 .Similar results were reported later [4,5] for the CÀC bond dissociation reaction (2) and [2+2] cycloadditions and CH 2 -[*] Prof. …”
supporting
confidence: 69%
“…In general it appears when a first-row atom or group X (X = B, C, N) is successively alkylated. Gilbert [3] found increasing errors of the B3LYP functional (up to 20 kcal mol À1 ) for the dissociation reaction (1) when R = H is replaced by CH 3 .Similar results were reported later [4,5] for the CÀC bond dissociation reaction (2) and [2+2] cycloadditions and CH 2 -[*] Prof. …”
supporting
confidence: 69%
“…[14,17,30,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Check and Gilberts analysis of homolytic CÀC bond breaking energies of methyl-substituted ethane show B3LYP to have increasing errors as the number of methyl group substitutions is increased. [60] We have recently tested a large number of density functionals by computing the Pople bond separation reaction energies of n-alkanes (propane through decane) and found that all functionals systematically underestimate the energy of these reactions.…”
Section: Computational Modelsmentioning
confidence: 99%
“…Similar conclusions were found by Yao and co-workers, who explored the accuracy obtained by a variety of hybrid functionals and coupled cluster treatments for calculating the BDEs. [37] The work of Feng et al is also worth mentioning since it concerns an assessment of BDEs using both composite ab initio methods and various DFT methods on a very complete dataset. Golden and co-workers further confirmed that the commonly used B3LYP method is insufficient for an accurate evaluation of BDEs and suggested other hybrid methods such as the KMLYP method, that yield rootmean-square (RMS) deviations that are close to the experimental error bars.…”
Section: Phenanthrene Dibenzoa C H T U N G T R E N N U N G [Cg]phenmentioning
confidence: 99%